Case Study: Comprehensive Midwifery Care of Mrs.I at RSU Bahagia Makassar - Surmayanti, Surmayanti; Jufri.P, Fitriana Jufri.P (Sean Institute, 2022)
The Maternity Maternal Mortality Rate (MMR) ) and Infant Mortality Rate (IMR). Are still relatively high in Indonesia. The various effort made by the government, oneif wich is trough Comprehensife Midwifery Care which consists of integrated Midwife Care starting from Pregnancy, Maternity, Neonatus, Postpartum, Family Planning (KB). Written using the Midwifery Care Documentation (ASKEB) and SOAP methods in descriptive and narative form, and continous assesmnet is carried out (Continuity of care). The subject of this research is Mrs. I, 27 years old at RSU Bahagia Makassar, the study was carried out on March 7 2022 to May 16 2022. From the results of the study on pregnancies wich were carried out 3 times, Mrs I have a high risk of experiencing chronich energy ddeficiency (KEK) where the Upper Arm Circumference (LILA) is <23,5 cm. At Maternity Mother Care Mrs. I experienced labor with a long second stage. At BBL care the baby Mrs. I had Low Birth Weight (LBW), and at Family Planning Care (KB) there were no complications and the mother wanted to use implant contraception. The conclusion in this study is that the practice is in accordance with the theory and there is no motive. Suggestions from the studies that have been carried out are to continue efforts to provide midwifery services to prevent complitation.